Evolution of oxidation during storage of crisps and french fries prepared with sunflower oil and high oleic sunflower oil - M. Martín-Polvillo; G. Márquez-Ruiz; N. Jorge; M. V. Ruiz-Mendez; M. C. Dobarganes (Grasas y Aceites)
Storage studies were carried out to define the behaviour of both conventional and high oleic sunflower oils in the industrial preparation of crisps and prefried french fries. Samples of crisps and prefried french fries were stored during 6 and 21 months, respectively, and evolution of oxidation was compared with that of the more saturated fats normally used for the preparation of both products, i.e., palm olein and hydrogenated rapeseed/palm oil mixture. Total oxidation compounds, α-tocopherol content, as well as monomeric and dimeric triglycerides, were quantitated in lipids from fried products after different time periods. Results obtained for crisps at room temperature indicated that only conventional sunflower oil underwent significant oxidation after 6 months. In the case of prefried french fries, maintained at freezer temperatures, no appreciable changes were found after 21 months storage, thus indicating that both sunflower oils can be good alternatives to saturated fats.